2016
DOI: 10.1074/mcp.m115.049338
|View full text |Cite
|
Sign up to set email alerts
|

ROS Homeostasis Regulates Somatic Embryogenesis via the Regulation of Auxin Signaling in Cotton

Abstract: Somatic embryogenesis (S.E.) is a versatile model for understanding the mechanisms of plant embryogenesis and a useful tool for plant propagation. To decipher the intricate molecular program and potentially to control the parameters affecting the frequency of S.E., a proteomics approach based on two-dimensional gel electrophoresis (2-DE) combined with MALDI-TOF/TOF was used. A total of 149 unique differentially expressed proteins (DEPs) were identified at different stages of cotton S.E. compared with the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 75 publications
6
39
0
1
Order By: Relevance
“…Regarding the hormonal interactions of H 2 O 2 , the salicylic acidtriggered embryogenesis was accompanied by H 2 O 2 production due to the inhibition of APX and CAT (Luo et al, 2001). In a recent proteomic study, several ROS-scavenging enzyme proteins were found to be induced in somatic embryos of cotton (Zhou et al, 2016). Suppressing the expression of specifically identified GhAPX proteins resulted in the inhibition of dedifferentiation, reflecting the involvement of ROS in the differentiation process.…”
Section: Ros-no Interplay During Seed Embryogenesismentioning
confidence: 99%
“…Regarding the hormonal interactions of H 2 O 2 , the salicylic acidtriggered embryogenesis was accompanied by H 2 O 2 production due to the inhibition of APX and CAT (Luo et al, 2001). In a recent proteomic study, several ROS-scavenging enzyme proteins were found to be induced in somatic embryos of cotton (Zhou et al, 2016). Suppressing the expression of specifically identified GhAPX proteins resulted in the inhibition of dedifferentiation, reflecting the involvement of ROS in the differentiation process.…”
Section: Ros-no Interplay During Seed Embryogenesismentioning
confidence: 99%
“…Furthermore, exogenous hydrogen application significantly reduced ROS levels and enhanced antioxidant enzyme activity in H 2 -treated PEMs (Figure S1). Considering that redox status is a crucial factor in determining plant development [31] and ROS homeostasis regulates somatic embryogenesis [32], we presume that the increased rate of active pro-embryogenic cells and normal somatic embryos may be, at least partially, a result of reduced ROS levels after H 2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As an excellent natural provider of fibre, cotton needs a reproducible and highly efficient plant regeneration scheme for transgenic research and genetic engineering. The morphological and molecular mechanisms of SE have been studied in cotton in our laboratory (Jin et al, 2014;Yang et al, 2012;Zhou et al, 2016). GhHmgB3-deficient hypocotyls dedifferentiate more rapidly but fail to differentiate into ECs (Hu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Auxin plays an important role in WUS expression, which is essential for embryonic stem cell fate determination during SE in Arabidopsis (Mayer et al, 1998;Su et al, 2009). Research has also demonstrated that the interactions between auxin, ethylene, gibberellic acid and stress response regulate SE (Wang et al, 2018;Zheng et al, 2013Zheng et al, , 2016Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%